FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN TIDAK SELAMAT PADA PEKERJA DI KETINGGIAN PROYEK TOL CIMANGGIS - CIBITUNG SEKSI 2 PT X TAHUN 2023 - Fahdli Rasyid, (2023)
The development of infrastructure in Indonesia is increasing rapidly, making the construction sector has a high risk of work accidents. Workers who do not comply with regulations can have an increased risk of work accidents, especially for workers at height. The preliminary study found 6 first aid cases (FAC) and 7 medical treatment cases (MTC). This study aims to determine the factors associated with unsafe actions on workers at the height of the Cimanggis - Cibitung Highway Section 2 PT X 2023. This research used a cross-sectional study design. A total of 87 altitude workers were selected as sampels by using a total sampling technic The research sampling technique used total sampling. Data were collected by using IFRC questionnaires. Data were analysed by using a chi-square test. The results showed 6.9% of workers perfomed unsafe actions. They was a significant relationship between training (p-value = 0.000), knowledge (p-value = 0.000), supervision (p-value = 0.029) with unsafe actions. Its Recommended to the companies to supervise workers at height on a regular basis. For workers will attend training and improve knowledge. Workers are required to participate in training to improve their knowledge.